Cross-species virulence strategies of mycobacterium Avium subsp. Paratuberculosis: Gene expression and infection progression in sheep and guanacos - Salgado, Miguel; Tejeda, Carlos; Steuer, Pamela; Moraga, Claudio A.; Radic Schilling, Sergio Javier; Corti, Paulo (My University, 2025)
Pathogenic bacteria adapt to their hosts modulating virulence-gene expression. This flexible and responsive virulence is frequently associated with the capacity of bacterial pathogens to infect a variety of host species, including wildlife and domestic animals. Mycobacterium avium subsp. paratuberculosis (MAP) is the causative agent of Johne's disease and infects a broad range of ruminant-like herbivores. While its virulence has been well-studied in livestock, its behavior in wildlife hosts remains poorly understood. By studying infection progression and virulence-gene expression, we gain important insights into how bacteria cause infection and how the host reacts. Here, we examine virulence of MAP isolates obtained from fecal samples of domestic sheep and guanaco (Lama guanicoe), including MAP infection progression and expression of six MAP genes, two oxidative stress response genes (katG, sodA) and four virulence-associated genes (impA, umaA1, papA2, kdpC). The progression of the infection was monitored using fecal shedding estimates as a proxy indicator. Compared to guanaco, sheep exhibited both noticeably higher MAP shedding and expression of all six genes. These results indicate that MAP modifies its expression profile in response to the host environment, and also to a possible host-specific transcriptional modulation of MAP. These data did not exclude guanaco as a potential source of infection for both their own species and for other MAP-susceptible species in the area. In mixed species-use landscapes, managing cross-species transmission and MAP persistence requires an understanding of these mechanisms.
Keywords: gene expression; oxidative stress; paratuberculosis; rt-qpcr; virulence; wildlife reservoirs